FDA Bioequivalence Standards - Yu, Lawrence X.; Li, Bing V.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This comprehensive reference provides an in-depth discussion on state-of-the-art regulatory science in bioequivalence. In sixteen chapters, the volume explores a broad range of topics pertaining to bioequivalence, including its origin and principles, statistical considerations, food effect studies, conditions for waivers of bioequivalence studies, Biopharmaceutics Classification Systems, Biopharmaceutics Drug Disposition Classification System, bioequivalence modeling/simulation, and best practices in bioanalysis. It also discusses bioequivalence studies with pharmacodynamic and clinical endpoints as well as bioequivalence approaches for highly variable drugs, narrow therapeutic index drugs, liposomes, locally acting gastrointestinal drug products, topical products, and nasal and inhalation products. FDA Bioequivalence Standards is written by FDA regulatory scientists who develop regulatory policies and conduct regulatory assessment of bioequivalence. As such, both practical case studies and fundamental science are highlighted in these chapters. The book is a valuable resource for scientists who work in the pharmaceutical industry, regulatory agencies, and academia as well as undergraduate and graduate students looking to expand their knowledge about bioequivalence standards.
1 Bioequivalence History -- 2 Fundamentals of Bioequivalence -- 3 Basic Statistical Considerations -- 4 The Effects of Food on Drug Bioavailability and Bioequivalence -- 5 Bio waiver and Biopharmaceutics Classification System -- 6 Bioequivalence of Highly Variable Drugs -- 7 Partial Area under the Curve: An Additional Pharmacokinetic Metric for Bioavailability and Bioequivalence Assessments -- 8 Bioequivalence for Narrow Therapeutic Index Drugs -- 9 Pharmacodynamic Endpoint-based Bioequivalence Studies -- 10 Clinical Endpoint Bioequivalence Study -- 11 Bioequivalence for Liposomal Drug Products -- 12 Bioequivalence for Drug Products Acting Locally within Gastrointestinal Tract -- 13 Bioequivalence for Topical Drug Products -- 14 Bioequivalence for Orally Inhaled and Nasal Drug Products -- 15 Bioequivalence: Modeling and Simulation -- 16 Bioanalysis.
Keywords: Medicine; Pharmaceutical technology; Biomedicine; Pharmaceutical Sciences/Technology.; Electronic books